A IMPLEMENTATION OF DANCE EXTRACURICULARS IN FORMING THE CHARACTER OF STUDENT CONFIDENCE AND DISCIPLINE AT MI MUHAMMADIYAH 01 TODANAN: PELAKSANAAN EKSTRAKURIKULER SENI TARI DALAM MEMBENTUK KARAKTER PERCAYA DIRI DAN DISIPLIN SISWA DI MI MUHAMMADIYAH 01 TODANAN - Rakanita Dyah Inesti; Yusuf; Dewi Permata Sari, Dewi (Jurnal Inovasi Pendidikan Madrasah Ibtidaiyah (JIPMI), 2024)
ABSTRACT The purpose of this study was to find out: (1) the implementation of dance extracurriculars in forming the self-confident and disciplined character of students at MI Muhammadiyah 01 Todanan Blora. (2) supporting and inhibiting factors in the implementation of dance extracurriculars in forming the self-confident and disciplined character of students at MI Muhammadiyah 01 Todanan Blora This research is a qualitative research, using field research (field research). The subjects of this study were madrasa teachers, dance instructors, and students. The primary sources were obtained from non-participant observations at MI Muhammadiyah 01 Todanan Blora and structured interviews with madrasa teachers, dance instructors, and students. Meanwhile, secondary sources were obtained from dance extracurricular documents and school history. The results of this study are: 1. Implementation of dance extracurriculars in shaping students' self-confidence and discipline. namely: A. Implementation of Dance Extracurriculars consisting of: 1) Planning stage, Butterfly dance extracurricular planning in consultation with MI Muhammadiyah 01 Todanan teachers. 2) The implementation stage, there are 5 stages of extracurricular dance implementation, namely explaining the purpose of body exercises and material, doing body exercises, entering the material stage, dividing students into several groups, and evaluating. B. The characters contained in the Dance Extracurricular are: the character of self-confidence and the character of discipline. 2. Factors inhibiting the implementation of extracurricular art dance (butterfly dance) in shaping the character of student self-confidence and discipline are as follows: A. The level of intelligence of students varies. B. Readiness of students. The supporting factors are as follows: Support fromstakeholder madrasah, partiesstakeholder MI provides full support for all dance extracurricular activities. Competent dance instructors and facilities in the form of costumes and equipment to support the extracurricular dance. Keywords: Extracurriculars, Dance, Butterfly Dance, Confident Character, Discipline Character.